Análise e correlação de registros de processos erosivos com dados pluviométricos - Mello, João Pedro Massari de [UNESP] (Universidade Estadual Paulista (Unesp), 2018)
News related to rains are commonly observed in physical or digital media and many are related to problems and damages caused to communities and citizens. Some of these events are related to linear erosions that develop as a result of heavy rains, and are, in a way, an interesting way of studying more current cases of erosive features and development, constituting a collection of information pertinent to both the academic area and the community. The general objective of this study was to analyze a series of erosion records and to associate with the rainfall índices. In this way, is presented a general and updated overview of the records of erosive processes mostly located in the southeast region, specifically of linear erosions, based on data collected in electronic newspaper reports, involving cases of erosions of various types. This work presents the results obtained, presented in the form of graphs, tables and photos, proving a visible correlation between the retroactive rainfall in 30 days and the erosive features that formed, allowing to evaluate the character of rain erosivity, according to the intensity, variation and duration. It was also considered the character of erodibility of the land, with the main conditioning factors: topography, declivity, vegetation cover and soil properties. Specific studies were carried out for the municipalities of Bauru/SP and Rio Claro/SP in order to analyze locally the action of linear erosive processes. Throughout the research, the contribution of rainfall to the emergence and growth of linear erosive features was observed. The data present a correlation of rainfall with linear erosions, although such erosive features form in a gradual process. It was evident that the treatment of situations of possible risk for linear erosive processes should be different from the management applied to landslides, since there is a difference in the speed of process development. Parallel to the process of erosivity and...

Notícias relacionadas às chuvas são, comumente, observadas em mídias físicas ou digitais e muitas estão relacionadas a problemas e danos causados às comunidades e aos cidadãos. Alguns desses eventos estão relacionados a erosões lineares que se desenvolvem em decorrências de fortes chuvas, constituindo uma maneira interessante de se estudar casos mais atuais de desenvolvimento e avanço de feições erosivas, constituindo um acervo de informações pertinentes tanto à área acadêmica quanto à comunidade. O objetivo geral deste estudo foi analisar uma série de registros de erosões e associar aos índices pluviométricos. Desta forma, é apresentado um panorama geral e atualizado de registros de processos erosivos majoritariamente situados na região sudeste, especificamente das erosões lineares, com base em dados levantados em notícias de jornais eletrônicos, envolvendo casos de erosões de diversas tipologias (sulcos, ravinas, voçorocas e erosões fluviais). Este trabalho expõe os resultados obtidos, apresentados na forma de gráficos, tabelas e fotos, comprovando uma correlação visível entre as chuvas retroativas em 30 dias e as feições erosivas que se formaram, permitindo avaliar o caráter de erosividade da chuva, conforme a intensidade, variação e duração. Foi também considerado o caráter de erodibilidade do terreno, com os principais fatores condicionantes: topografia, declividade, cobertura vegetal, uso do solo e variação das propriedades do solo. Foram realizados estudos específicos de casos para os municípios de Bauru/SP e Rio Claro/SP a fim de se analisar localmente a ação dos processos erosivos lineares. Foi denotada ao longo da pesquisa a contribuição das chuvas para o surgimento e crescimento das feições erosivas lineares. Os dados apresentam uma correlação das chuvas com as erosões lineares, apesar de tais feições erosivas se formarem num processo gradual. Ficou evidente que o tratamento...
Keywords: Erosão; Solos - Erosão; Chuvas; Brasil, Sudeste; Bauru (SP); Rio Claro (SP)